KESEPANCARAN (HOMOLOGI) LEGIONELLA PNEUMOPHILA JARINGAN DISTRIBUSI AIR DAN PNEUMONIA NOSOKOMIAL - Noormartany . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
L. pneumophila is one of the nosocomial pneumonia causes that contaminated hospital water distribution system. The aim of this study was to determine the homology between L. pneumophila 16S rRNA base sequence found in the water distribution systemand the sequence derived from the sputum of nosocomial pneumonia patients identified at RSHS Bandung as well as the homology of L. pneumophila 16S rRNA found in the same system network. The study also include the nosocomial pneumonia patients at RSHSBandung with L. pneumophila from GenBank. The research using descriptive bioinformatics BLAST method by comparative analyticapproach, which performed from April 2006 to February 2008. The material consists of 60 biofilm samples from water distributionsystem and pneumonia nosocomial patient’s sputum is positive L.pneumophila from water distribution system in her/his room. Inthe result was found: out of the 60 biofilm samples from the water distribution system, there are seven (7) L. pneumophila positivePCR and culture. During the 12 months of observation, there is only one (1) out of 31 pneumonia nosocomial patients with positively L. pneumophila PCR and culture. The conclusion so far can be mentioned that: The water distribution system in RSHS for patient roomsmay become the source for nosocomial pneumonia transmission of L. pneumophila and also was detected a new species of L. pneumophilathat is genetically different from that has been found in GenBank.